Aggregation‐induced emission luminogen: A new perspective in the photo‐degradation of organic pollutants. Issue 2 (27th April 2020) - Hu, Zhen; Li, Ying; Kang, Miaomiao; Islam, Md. Monarul; Chen, Mengsi; Zhang, Jun; Xiao, Ye; Feng, Xing; Redshaw, Carl; Zhang, Menglong; Chen, Qing; Xie, Sheng; et al.
Abstract: Both the variety and uniqueness of organic semiconductors has contributed to the rapid development of environmental engineering applications and renewable fuel production, typified by the photodegradation of organic pollutants or water splitting. This paper presents a rare example of an aggregation‐induced emission luminogen as a highly efficient photocatalyst for pollutant decomposition in an environmentally relevant application. Under irradiation, the tetraphenylethene‐based AIEgen (TPE‐Ca ) exhibited high photo‐degradation efficiency of up to 98.7% of Rhodamine B (RhB) in aqueous solution. The possible photocatalytic mechanism was studied by electron paramagnetic resonance and X‐ray photoelectron spectroscopy spectra, electrochemistry, thermal imaging technology, ultra‐performance liquid chromatography and high‐definition mass spectrometry, as well as by density functional theory calculations. Among the many diverse AIEgens, this is the first AIEgen to be developed as a photocatalyst for the degradation of organic pollutants. This research will open up new avenues for AIEgens research, particularly for applications of environmental relevance. Abstract : This paper presents a rare example of aggregation‐induced emission luminogens (AIEgens) as a highly efficient photo‐catalyst for pollutant decomposition in an environmentally relevant application.